Explosion sensitivity and severity of south east asian coals - Wan Zaiton, Wan Sulaiman (2014)
There is a risk of coal dust explosion to industries mainly in cement processing industries, power plants as well as other activities associated with handling of pulverized coals. This study aims to investigate the effect of chemical properties of the South East Asian coals on the explosibility of three samples of coal dust which were bituminous Bayan, sub bituminous Tanito and Philippine coals. The minimum explosion concentration (MEC), maximum explosion overpressure (PPmax) and dust deflagration index (K) were determined to compare the fundamental data on coal dust characteristics. The explosion experiment was carried out in a Siwek 20 L spherical chamber. The chemical properties of investigated coals such as moisture content, volatile content, fixed carbon content and ash content were analysed by proximate analysis and Thermogravimery analysis (TGA). Both moisture content and ash content of Philippine and Tanito coals were approximately 10 wt %. The coals were hardly exploded at high moisture content and low content of ash gave no influence on explosibility of the coals. High volatility at approximately 40 wt % increases the severity of the dust explosion. Analysis of fixed carbon content and calorific value showed that the coals were in the low ranking class with fixed carbon and calorific value at approximately 40 to 45 wt % and 25000 kJ/kg, respectively. The MEC for the Bayan, Tanito, and Philippine coal dust were 350 kg/M3, 400 kg/m3 , and 315 kg/m3 , respectively. The high results of MEC for the coals were due to non-uniform particle sizes and high moisture content. The Pmax for Bayan, Tanito, and Philippine coal dust were 10.15 bar, 7.35 bar and 10.4 bar, respectively. The for Bayan, Tanito, and Philippine coal dust were 48.04 bar.nVs, 16.83 bar.rn/s, and 52.39 bar.niJs, respectively. High volatility was the reason of high Prnax and hence